Gender and trade in Africa: Case study of Niger - Fofana, Ismaël; Odjo, Sunday P.; Traoré, Fousseini (International Food Policy Research Institute, 2019)
Trade is positively associated with economic growth as it expands market opportunities, increases income earnings, and improves livelihoods. However, there are prerequisites to fully seize the opportunities offered by trade—among others, less discriminatory practices. Countries with less discriminatory practices—such as fewer gender-based labor market disparities— enjoy higher benefits from trade openness. Trade can refer to the exchange of goods and services within a given country (that is, internal trade) as well as between two or more countries (that is, external trade). This study focuses on the latter; trade is used to refer to external trade hereon.